Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Review: 14

Answer

(2, -1)

Work Step by Step

Substitute the equation for y in terms of x into the second equation: 2x - 3(3x - 7) = 7 Solve for x: 2x - 9x + 21 = 7 -7x + 21 = 7 -7x = -14 x = 2 Let x = 2 in the first equation to solve for y: y = 3(2) - 7 = -1 Check the solution (2, -1) in the second equation: 2(2) - 3(-1) = 7 4 + 3 = 7 7 = 7; True
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.